Grounding-line fan formation during an Early Holocene readvance of Aldegondabreen, Svalbard. - Jóhannesdóttir, Jóhanna Kristín (UiT Norges arktiske universitet, 2021)
In this study, two ridge-shaped cross-valley sedimentary landforms, in the lower forefield of Aldegondabreen, a small valley glacier on the west coast of Spitsbergen, Svalbard, were studied to reconstruct the Holocene glacial history of Aldegondabreen prior to the Little Ice Age. Sedimentological and geomorphological methods were used in conjunction with radiocarbon dating to examine the sediments in the landforms. Three sedimentary lithofacies associations were identified within the studied landforms of the lower forefield. 1) Gravel with small bivalve shell fragments formed in a grounding-line fan, 2) glaciotectonised gravel formed in a subaerial glaciofluvial outwash plain, and 3) glaciogenic sediments, including subglacial till with supra- and englacial components, and glaciotectonised marine sediments. The results suggest that Aldegondabreen readvanced in the Early Holocene into the shallow fjord during a relative high sea level. The maximum age for this event is suggested to be 10.79 cal. ka BP, constructed with radiocarbon dating of bivalve shells and fragments from glacially overridden marine sediments in the forefield. It is proposed that during this Early Holocene readvance, a grounding-line fan formed at the grounding zone of the tidewater glacier. The minimum ice margin position of the glacier during this advance was at least 2 km beyond the modern ice margin (2020) constructed with the location of the grounding-line fan deposit. The data from this study adds to the Late Glacial - Early Holocene glacial record from Svalbard and provides new insights into pre-LIA Holocene glacial history of Aldegondabreen.